Éducation environnementale et programmes d’alphabétisation au Burkina Faso - Maxime Compaore (VertigO, 2003)
Burkina Faso, a sahelian country, has an economy essentially based upon agriculture. About 80% of the population is illiterate and live on agriculture and stock breeding in a climatic context which is not always favourable. In its history, the country has experienced cases of drought which has contributed to increase the population poverty and misery. The water issue is central for this poor country, enclosed in the center of Western Africa. Every year, water supply shortage is very frequent as well in the rural milieu as in in the urbain one. In such a context, how to promote an education centered on a good management of the scarce existing resources? One of the solutions recommended for the reduction of poverty in general and the endogeneous development in particular rests in the organization of litteracy campaigns. The approach used is a participatory one and concerns very sensitive subjects such as water, hygiene, health, etc. Our paper look on the one hand into the taking into account of water issue in the organization of literacy lessons and on the other hand into the impact of literacy compaigns on the populations behaviours with regard to the set of water supply problems.